Two girls and a guy - Toback, James; Downey, Robert, 1965-; Graham, Heather, 1970-; Wagner, Natasha Gregson, 1970-; Pressman, Edward R.; Hanley, Chris; Fox Searchlight Pictures; Muse Productions; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2000)
When two young women realize that they have the same boyfriend, they take him on the wildest ride of his life.
Originally produced as a motion picture in 1998.
Special features: commentary by director James Toback, Robert Downey, Jr. and Natasha Gregson Wagner ; theatrical trailer.
Aspect ratio 1.85:1. Anamorphic widescreen.
Robert Downey, Jr., Heather Graham, Natasha Gregson Wagner.
Rated R ; Added value material not rated.
DVD, Dolby digital.
Keywords: Man-woman relationships -- Drama; Dating (Social customs) -- Drama; Feature films; Video recordings for the hearing impaired; Spanish language materials